(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2020)
The Naskah Kitab Hukum manuscript issued by Thomas Stamford Raffles in 1814 is one of the important manuscripts in the history of a judicial system in Indonesia. The manuscript was published because Raffles, upon his early days of duty, noticed that the existing judicial system in Java was complicated and confusing, constituted in the formalities of the Roman law. This article presents a study of how the Naskah Kitab Hukum became a means of social engineering of the inhabitants of Java through at least three ways: (1) legislation process before the issuing of regulation, (2) accommodating the social cohesion of Java inhabitants into the regulation and (3) domestication of English legal terms which were not familiar to the Java inhabitants.